Pengaruh CSRr Dan GCG Terhadap Nilai Perusahaan Dengan Profitabilitas Sebagai Variabel Moderasi - Azima, Athiyah Farah; Aristi, Mentari Dwi; Ramashar, Wira (Jurnal Ekonomika Dan Bisnis (JEBS), 2024)
The purpose of this study was to determine the effect of Corporate Social Responsibility (CSR) and Good Corporate Governance (GCG) on firm value with profitability as a moderating variable in Energy Sector Companies listed on the IDX in 2019-2022. The population in this study were all companies included in the Energy Sector listed on the Indonesia Stock Exchange (IDX) during 2019-2022. The total population in this study was 80 companies. Sample withdrawal using purposive sampling, from the selection process resulted in a sample of 12 companies. The total data during the study period was 48 observation data. The type of data used is secondary data sourced from the company's financial statements. Data analysis using multiple linear regression and moderation regression analysis. The results showed that Corporate Social Responsibility (CSR) has a positive and significant effect on firm value. Good Corporate Governance (GCG) has a positive and significant effect on firm value. Profitability moderates the effect of Corporate Social Responsibility (CSR) on firm value, but profitability does not moderate the effect of Good Corporate Governance (GCG) on firm value.